Regression models in the assessment of the relationship between body posture in the sagittal plane and SEMG of the spine rectifier in children at a younger school age - Wilczyński, Jacek; Karolak, Przemysław; Janecka, Sylwia; Jasek, Paulina (Journal of Education, Health and Sport, 2019)
The aim of the study was to create regression models for the analysis of the relationship between posture defects in the sagittal plane and SEMG of the spine rectifier in children with scoliotic lesions. The shape of the spine was assessed using the optoelectronic method Diers formetric III 4D. The SEMG analysis was performed using the Noraxon TeleMyo DTS 12 channel camera. The research was carried out in 2017 at the Posturology Laboratory at the Faculty of Medicine and Health Sciences of UJK in Kielce. The most important and statistically significant predictor of the body posture in the sagittal plane and the frequency of the ridge extensor examined in various positions in the group of scoliotic postures turned out to be the variable lower limb up the right breast segment (p = 0.01). In the case of the SEMG amplitude, the most important and statistically significant predictors in the group of scoliotic attitudes turned out to be variable lower limbs upward lumbar segment right side (p = 0.02) and standing position lumbar segment left side (p = 0.03). The SEMG test enables the control of muscle balance and allows to avoid the improper deepening of muscle asymmetry, resulting in the stimulation of disturbing forces.